2015
DOI: 10.1111/evj.12396
|View full text |Cite
|
Sign up to set email alerts
|

Intrafollicular treatment with prostaglandins PGE2 and PGF inhibits the formation of luteinised unruptured follicles and restores normal ovulation in mares treated with flunixin‐meglumine

Abstract: The article summarizes the results of several studies, which highlight the relevance of prostaglandins E2 (PGE2) and F2 (PGF2a) during the ovulatory process in mares and their implication in the pathogenesis of luteinized unruptured follicles. Following the preovulatory luteinizing hormone (LH) surge, the two prostaglandins are synthesized in granulosa cells. They subsequently trigger a cascade of events that lead to ovulation. The exogenous administration of intrafollicular PGE2 and PGF2a can induce follicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…It has been reported that intrafollicular prostaglandins increased 36 h after hCG treatment in mares (Watson & Sertich 1991, Sirois & Dore 1997. A recent study (Martínez-Boví & Cuervo-Arango 2015) demonstrated the importance of prostaglandins in the ovulation process in mares by using intrafollicular injection of a supra-physiological cocktail of PGE 2 and PGF 2 a (500 and 125 mg, respectively) to reverse the anovulatory effects of FM. Another novel finding from our study was the increased intrafollicular PGE 2 :PGF 2 a ratio in mares with induced LUFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that intrafollicular prostaglandins increased 36 h after hCG treatment in mares (Watson & Sertich 1991, Sirois & Dore 1997. A recent study (Martínez-Boví & Cuervo-Arango 2015) demonstrated the importance of prostaglandins in the ovulation process in mares by using intrafollicular injection of a supra-physiological cocktail of PGE 2 and PGF 2 a (500 and 125 mg, respectively) to reverse the anovulatory effects of FM. Another novel finding from our study was the increased intrafollicular PGE 2 :PGF 2 a ratio in mares with induced LUFs.…”
Section: Discussionmentioning
confidence: 99%
“…In mares, flunixin meglumine (FM) at a dose rate of 1.7 or 2.0 mg/kg body weight has been shown to induce LUFs in 73-83% of mares respectively , Cuervo-Arango & Domingo-Ortiz 2011. Furthermore, intrafollicular administration of prostaglandins has successfully prevented FM-induced LUF formation, allowing subsequent ovulation and conception in mares (Martínez-Boví & Cuervo-Arango 2015). In women, NSAIDs have been used experimentally to inhibit ovulation, and a dose-dependent effect has been observed (Athanasiou et al 1996, Bata et al 2006, Jesam et al 2010, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that intrafollicular administration of PGE2 and PGF2 α to mares in early to mid‐oestrus without the simultaneous treatment with an inductor of ovulation would induce follicle collapse was supported by the results of this study, as the majority of treated mares (4 of 6) had follicle collapse within 12 h of treatment. The PGE2 and PGF2 α treatment used in this experimental protocol was based on a recent study in which 100% of mares treated with a prostaglandin inhibitor ovulated after intrafollicular injection of this solution (Martinez‐Bovi and Cuervo‐Arango ). The protocol described in this current study seemed to induce follicle collapse in mares before it would have been expected according to the LH ovulatory surge.…”
Section: Discussionmentioning
confidence: 99%
“…The time of injection was set as Hour 0. The PGE2/PGF2 α dose and ratio were chosen according to a previous study (Martinez‐Bovi and Cuervo‐Arango ) in which this protocol successfully induced follicle collapse within 12 h of treatment in 100% of mares. The intrafollicular puncture was performed with the mare restrained in the stocks, after sedation with an i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Following intramuscular administration of the manufacturer's recommended dose of PGF2a (5 mg), slight adverse side effects can be observed in some mares (about 10 %), such as sweating, diarrhea, or colic (Irvine 1993). However, when cloprostenol was administered intravenously (250 µg, manufacturer's recommended dose), severe adverse side effects such as ataxia and profuse diarrhea as well as sweating were noted in 100 % of treated mares (Cuervo-Arango 2011).…”
Section: Introductionmentioning
confidence: 99%